Prevalence and socio-demographic correlates of attention-deficit/hyperactivity disorder among Albanian students - Flora Zeqaj Lamçja; Eliona Sula; Elona Prifti; Paola Pina; Kaçe Baushi; Sabina Tosuni (Institute of Advanced Engineering and Science, 2026)
Attention-deficit/hyperactivity disorder (ADHD) may significantly interfere with daily functioning, particularly among nursing students who face high academic stress and demanding clinical schedules. This study aimed to assess prevalence of screening-positive ADHD symptoms and associated factors among 370 Albanian nursing students. A descriptive cross-sectional study was conducted using the adult ADHD self-report scale (ASRS) v1.1. Data analysis included descriptive statistics and inferential tests (such as χ² and analysis of variance (ANOVA)), with significance set at p<0.05. Results indicated that 11.7% of students without a prior ADHD diagnosis screened positive for high ADHD symptom levels. Low to moderate symptoms were recorded by approximately 59% of participants in both ASRS part A and part B, and by 65% based on the total score. No significant associations were found between ADHD symptom severity and gender, living situation, residence, or peer integration (p>0.05). However, symptom severity was significantly associated with help-seeking behavior (p=0.009) and daily life difficulties, particularly economic challenges (p=0.02), with higher symptoms more common among students relying on themselves-coping strategies. Based on these results, targeted interventions such as cognitive-behavioral workshops, academic coaching, and psychoeducational programs could help Albanian nursing students develop organizational and time-management skills, improve emotional regulation, and enhance academic performance.